Application of focused ultrasound in the treatment of epilepsy - S. G. Burd; A. V. Lebedeva; G. G. Avakyan; Yu. V. Rubleva; I. V. Senko; N. V. Pantina; A. V. Yurchenko; I. I. Kovaleva (Эпилепсия и пароксизмальные состояния)
The high prevalence of pharmacoresistant epilepsy requires the use of nonpharmacological, including surgical approaches to the treatment of this disease. The surgical methods currently used to treat epilepsy (resection, stimulation, and disconnection) carry certain risks of developing intra- and postoperative complications. The technique of magnetic resonance-guided focused ultrasound (MRgFUS) may be an alternative to traditional neurosurgical interventions. Currently, MRgFUS is successfully used in the treatment of essential tremor and Parkinson’s tremor. As the literature data show, the use of focused ultrasound is a promising method in the treatment of epilepsy. It has been reported about successful FUS application for neuromodulation in animal epilepsy models. Studies related to FUS ablation of epileptogenic foci, neuromodulation in humans with epilepsy are currently underway. The technique of locally increased permeability of the blood-brain barrier after FUS, used for the treatment of brain oncological diseases and neurodegenerative disorders is also of interest in the targeted delivery of antiepileptic drugs. However, some experimental works are contradictory, and the lack of large-scale studies of MRgFUS in patients with epilepsy requires further investigation of this technique and its effectiveness.